Dampak Penerapan Kurikulum Merdeka Terhadap Etnografi Kokurikuler Siswa Di SMPN 4 Jember - Devi Aryanti (Satya Widya, 2024)
The Merdeka Curriculum has been gradually implemented at SMPN 4 Jember. This research aims to assess the impact of the implementation of the Merdeka Curriculum on students' extracurricular activities at SMPN 4 Jember. Qualitative data were collected through interviews and field observations. The results of the observations indicate a positive improvement in students' extracurricular activities following the adoption of the Merdeka Curriculum. Students have become increasingly enthusiastic about developing their potential in various extracurricular activities. This research underscores the importance of the flexibility of the Merdeka Curriculum in providing students with opportunities to grow beyond the core subjects. Beyond academic achievements, the curriculum has played a pivotal role in cultivating well-rounded individuals who are not only academically proficient but also socially aware and confident in their abilities. This study serves as a testament to the positive impact of the Merdeka Curriculum on students' extracurricular activities and their broader educational experience at SMPN 4 Jember.